Makan secara Emosional dan Stres Psikologis: Mengungkap Perjuangan Tersembunyi Mahasiswa Internasional di Surabaya: Emotional Eating and Psychological Distress: Unveiling the Hidden Struggles of International Students in Surabaya - Ningtyas, Nisaus Shofi Ayu; Isaura, Emyr Reisha (Universitas Airlangga, 2024)
Background: International students often face significant adaptation challenges in new academic settings, leading to increased psychological stress, which may affect their emotional well-being and eating habits. Emotional eating is commonly triggered by stress and may contribute to the development of abdominal obesity, which is a serious health concern associated with a higher risk of metabolic and cardiovascular diseases. Objectives: This study aims to examine the presence of psychological stress and the incidence of emotional eating among international students. Methods: A cross-sectional study was conducted at Airlangga University in April 2024 with 130 international student respondents from a total of 165 international students recorded, who provided consent and met the inclusion criteria. Data were collected and analyzed descriptively, and statistical testing was conducted using Spearman’s correlation, setting the significance level at p-value <0.05. Results: Most respondents were female (54.62%), undergraduate students (60.00%), Malaysians (57.70%), and had a median waist circumference of 82.59 cm. Psychological stress was associated with emotional eating behavior, as indicated by significant correlations between the subscales of depression, anxiety, and stress as well as the total Depression Anxiety Stress Scales (DASS) score and the total Dutch Eating Behavior Questionnaire Emotional Eating (EE) score (p <0.001). Conclusions: International students experiencing psychological stress during their studies are more likely to engage in emotional eating behaviors, which can subsequently increase their potential for body size changes if not balanced with increased calorie burning.